Metal-Free One-Pot Chemoselective Thiocyanation of Imidazothiazoles and 2-Aminothiazoles with in situ Generated N-Thiocyanatosuccinimide - Kadam, Shuddhodan N.; Ambhore, Ajay N.; Hebade, Madhav J.; Kamble, Rahul D.; Hese, Shrikant V.; Gaikwad, Milind V.; Gavhane, Priya D.; Dawane, Bhaskar S. (Synlett, 2018)
A chemoselective thiocyanation of imidazothiazoles and 2-aminothiazoles with use of in situ generated N-thiocyanatosuccinimide (NTS) at room temperature is described. The protocol offers mild reaction conditions and high chemoselectivity for electrophilic substitution in imidazothiazoles over nucleophilic substitution. This method provides metal-free and easy conversion of imidazothiazoles and 2-aminothiazoles into their corresponding C-3 and C-5 thiocyanates, respectively, in good to excellent yield. The present protocol also offers the effective thiocyanation of bifunctional imidazothiazoles containing aliphatic –OH and C(sp2)–H bond functionalities.
Keywords: N-thiocyanatosuccinimide; thiocyanation; imidazothiazoles; 2-aminothiazoles; PEG-400